E-Voting dan Kualitas Demokrasi: Studi Komparatif Estonia dan India dengan Pendekatan Most Different Systems Design - Nabila Athiyah Rohmah (Journal of Administration, Governance, and Political Issues, 2026)
This study analyzes the implementation of e-voting as part of the smart governance transformation, which raises profound normative dilemmas regarding election integrity, public trust, and power relations. The shift from paper-based voting to digital formats offers efficiency and increased access to participation, but at the same time presents serious challenges in terms of public verification, cybersecurity, and the protection of voters' personal data. Rejecting the view of technological determinism, this study narratively compares how technopolitical configurations and institutional designs in Estonia and India shape the quality of democracy, particularly in terms of transparency, participation, and accountability. This research uses a comparative qualitative method with a Most Different Systems Design (MDSD) approach, comparing Estonia as a pioneer of internet voting based on high institutional trust and India as a user of Electronic Voting Machines (EVM) operating in a context of political fragmentation and declining public trust. The analysis is based on a synthesis of the Technopolitics and Rational Choice Institutionalism frameworks, which view technology as a political artifact resulting from the rational calculations of political actors. The findings show that the impact of e-voting on the quality of democracy is not determined by the type of technology, but rather by the technopolitical configuration, institutional design, and rationality of political actors. E-voting functions as a mediating variable that reinforces existing institutional conditions, so its success is highly dependent on the political context of each country.